Novos ambientes educacionais: desafios do uso das tecnologias educacionais inovadoras no contexto escolar - Puntel, Diane Roehrs; Muller, Liziany; Rech, Aline Pereira de Arruda (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Identify the main challenges in the presence of technology in the school environment is the main objective of this article. The methodology was based on an exploratory qualitative approach with a constructivist paradigm. The first action designed to instigate reflection of teachers and students was watching the video: You cannot be my teacher, available at: http://www.youtube/watch?v=R1KalH1YbM. As an instrument for data collection,it was used a questionnaire with open and closed questions for students and teachers from 5th to 8th grade of State High School Tomas Garcia da Costa in Lagoão / RS.The results indicate that most students have access to technology. They cited the computer lab, as the feature that most motivates, awakens the attention and helps the understanding of the contents in the school environment. All teachers agreed that classroom with blackboard and chalk just cannot be the only mediator of the process of teaching and student learning. They also said that they use the computer / internet as a form of recreation, but also as a tool for finding educational resources (videos, pictures, songs, articles, maps, etc.) to improve their teaching.